Antimicrobial Activity of Water-Soluble Silver Complexes Bearing C-Scorpionate Ligands - Abdallah G. Mahmoud; Sílvia A. Sousa; M. Fátima C. Guedes da Silva; Luísa M. D. R. S. Martins; Jorge H. Leitão (MDPI AG, 2024)
The novel hydrosoluble silver coordination polymer [Ag(NO3)(μ-1κN;2κN',N"-TPMOH)]n (1) (TPMOH = tris(1H-pyrazol-1-yl)ethanol) was obtained and characterized. While single crystal X-ray diffraction analysis of compound 1 disclosed an infinite 1D helical chain structure in the solid state, NMR analysis in polar solvents confirmed the mononuclear nature of compound 1 in solution. Compound 1 and the analogue [Ag(μ-1κN;2κN',N"-TPMS)]n (2) (TPMS = tris(1H-pyrazol-1-yl)methane sulfonate) were evaluated with regard to their antimicrobial activities towards the Gram-negative Escherichia coli, Pseudomonas aeruginosa, and Burkholderia contaminans, the Gram-positive Staphylococcus aureus, and the fungal species Candida albicans and Candida glabrata. Compound 1 exhibited minimal inhibitory concentration (MIC) values ranging from 2 to 7.7 µg/mL towards the tested Gram-negative bacteria, 18 µg/mL towards the Gram-positive S. aureus, and 15 and 31 µg/mL towards C. albicans and C. glabrata, respectively. Compound 2 was less effective towards the tested bacteria, with MIC values ranging from 15 to 19.6 µg/mL towards the Gram-negative bacteria and 51 µg/mL towards S. aureus; however, it was more effective against C. albicans and C. glabrata, with MIC values of about 6 µg/mL towards these fungal species. The toxicity of compounds 1 and 2 was assessed by evaluating the survival of the Caenorhabditis elegans model organism to concentrations of up to 100 µg/mL. The value of 50% lethality (LD50) could only be estimated as 73.2 µg/mL for compound 1 at 72 h, otherwise LD50 was >100 µg/mL for both compounds 1 and 2. These results indicate compounds 1 and 2 as novel silver complexes with interesting antimicrobial properties towards bacterial and fungal pathogens.